EMPLOYEE VALUE PROPOSITION (EVP) DEVELOPMENT TO SUPPORT INTERNATIONALIZATION STRATEGY IN THE CONTEXT OF DIGITAL AND DEMOGRAPHIC CHANGES - LUCHKO, Dmytro; ZELENEVYCH, Volodymyr (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines and analyzes recent research on the formation of Employee Value Proposition (EVP) by Ukrainian and international companies in the context of internationalization processes, identifying key trends and challenges of digital transformation and demographic changes. Based on the research, the main aspects to consider for developing effective human capital management strategies in the international environment are highlighted. EVP is defined as a key element of companies’ internationalization strategy, involving the integration of compensation, development and cultural aspects into the goals of attracting and retaining talent in global markets. Implementing cultural adaptation of EVP, introducing digital HR technologies and taking into account the expectations of different generations of employees contributes to the successful entry of companies into international markets and enhancing their competitiveness. However, challenges such as balancing global consistency and local relevance of EVP, managing expectations of a multigenerational workforce, ensuring authenticity of employer promises require attention. This approach underscores the importance of engaging management personnel in implementing EVP and convincing them of its positive impact on the overall success of the company in international markets. The integration of EVP principles into business activities promotes their sustainable development in international markets, enhances their reputation as an employer, facilitates the attraction of critical talent and supports internationalization strategy in a turbulent business environment. Research results confirm the growing interest of Ukrainian enterprises in integrating EVP into international expansion strategies, especially in the context of European integration and digital transformation.